A relação entre o Spread Bancário e os principais indicadores econômicos - Nosse, Nicole Kimie Kawakata Paz (Brasil, 2024)
The banking spread stands out as one of the most relevant economic indicators, representing the difference between the cost of raising funds by banks and the interest rates charged on loans. Spread variations can have a significant impact on the entire economy, directly influencing prices and access to credit. In this context, this study aims to analyze the relationship between banking spreads and key macroeconomic variables in 61 countries in 2021, during the height of the COVID-19 pandemic. The central objective is to understand the factors that determine banking spreads in a global context marked by unprecedented economic challenges. To this end, first, a bibliographical review of the main studies on the topic and formulation of initial hypotheses is carried out. To achieve this objective, a comprehensive literature review on the topic was carried out, followed by the formulation of hypotheses to be tested. The hypotheses were validated or refuted through an inferential statistical survey, using Gretl software. The empirical study revealed that GDP per capita has a negative and significant relationship with the banking spread, which can be explained by a higher level of economic development, which generally leads to greater efficiency in the financial system and lower cost of raising funds. resources for banks. On the other hand, the interest rate has a positive and significant relationship with the banking spread. Finally, banking concentration did not have a significant influence on banking spread in the data analyzed.